Pigmented skin patches without scleroderma as a predominant clinical symptom revealing systemic sclerosis. (1st June 2016) - Darrigade, A. S.; Vedie, A. L.; Gauthier, C.; Cario‐André, M.; Taieb, A.; Truchetet, M. E.; Constans, J.; Seneschal, J.
Summary: Skin induration remains the major clinical symptom of systemic sclerosis (SSc), an autoimmune disease with potentially life‐threatening visceral involvement. However, skin induration can be absent in some patients, making the diagnosis difficult to confirm and leading to delay in management. Skin pigmentation abnormalities have been reported in patients with SSc, and can be important to recognize for diagnosis. We report two patients who developed hyperpigmented skin patches without any sign of scleroderma, as a major clinical skin symptom of incipient SSc.